2016
DOI: 10.1186/s13570-016-0050-4
|View full text |Cite
|
Sign up to set email alerts
|

Are there options outside livestock economy? Diversification among households of northern Kenya

Abstract: Income diversification has been hailed by some policy-makers as an important ingredient for building pastoral resilience. This study applied the sustainable livelihood approach to establish the determinants of diversification among pastoral households of Turkana and Mandera Counties. In these Counties, 300 and 362 households, respectively, were identified through multi-stage sampling. A participatory wealth-ranking method was used to categorize the sampled households into three poverty levels: poor, middle and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…In a study that examines the relationship between income diversification and household welfare in Zimbabwe, Ersado found that households living in rural areas with highly variable rainfall were more likely to have a large number of income sources, which was consistent with the idea of income diversity serving as a risk management strategy [14]. Watete et al pointed out that improved education levels and better access to water are important factors in encouraging adoption of non-farm-based income-generating activities [8]. Guvele also pointed out that households, under the drought condition, could more quickly recover from the drought by increasing their sources of income and realized that diversifying income sources was an effective risk transfer strategy [9].…”
Section: Income Diversification As a Risk Management Strategymentioning
confidence: 78%
See 2 more Smart Citations
“…In a study that examines the relationship between income diversification and household welfare in Zimbabwe, Ersado found that households living in rural areas with highly variable rainfall were more likely to have a large number of income sources, which was consistent with the idea of income diversity serving as a risk management strategy [14]. Watete et al pointed out that improved education levels and better access to water are important factors in encouraging adoption of non-farm-based income-generating activities [8]. Guvele also pointed out that households, under the drought condition, could more quickly recover from the drought by increasing their sources of income and realized that diversifying income sources was an effective risk transfer strategy [9].…”
Section: Income Diversification As a Risk Management Strategymentioning
confidence: 78%
“…Table 3 shows that the education level of the household head is significantly and positively related to the number of income sources, as studies [19,20] have explained that high education levels open the window to different economic activities. Good education means engaging in more diverse activities and yields greater chances of earning more money [8]. The results also reveal that rural households with a small proportion of children and elderly people tend to diversify income sources, since a greater proportion of children of household members means that fewer family members are able to engage in agricultural production or migrant workers.…”
Section: Determinants Of Income Diversitymentioning
confidence: 88%
See 1 more Smart Citation
“…7 Similar to other communities affected by climate change, susceptibility to addiction, anxiety, and emotional distress caused by their reduced resilience is also on the increase. 1,3,7 Another outcome of decreased revenue from animal husbandry is an increase in fishing. Locals refer to Lake Turkana as a "free garden" from which anyone can earn a living.…”
Section: Sources Of Livelihoodmentioning
confidence: 99%
“…[3][4][5] Evidence supports the notion that underresourced communities, like pastoralists with limited livelihood alternatives, experience climate change disproportionately. 2 This editorial reflects on our six-week period of data collection in Turkana County, Kenya.…”
mentioning
confidence: 99%